Deconstructing taurine culture in Ecuador for animal rights consolidation - Morales Naranjo, Viviana (2020)
Bullfighting represents a manifestation of Spanish ideological colonization since it caused the collective consciousness to normalize a practice based on cruelty towards the feelingbeings. In order to deconstruct colonial thinking that revolves around bullfighting, the aim of this research is to demonstrate that there are a number of ethical, ethological and legal foundations aimed at making the foundations of animal ethics. The methodology used for this work is the sociology of absences and the sociology of the emergencies of Boaventura de Sousa Santos, since it is intended to highlight the epistemological weaknesses that underpin bullfighting, for this reason, explain the ethical, technical and legal bases that enable the bull to be achieved. The conclusions of this research are as follows: 1. Spanish colonization induced the acceptance of practices of cruelty towards non-human sinsient beings by the mestize culture, justifying itself in art, 2. the foundations of ethics animal justify the protection of the bull de lidia in its capacity to be feeling, 3. the positivization of animal rights must be accompanied by the moral change of citizens with regard to the treatment that the bull must receive.